Respiratory Function and Blood Gases Transport State at Experimental Hypoxia: Ozone Therapy Correction (Ozone Therapy Global Journal, 2012)
In condition of reproduction of hemorrhagic shock according to Wigger's experimentalmodel, the efficacy of systemic use of ozonotherapy together with infusion therapy ofhypovolemic con ditio n. It has been sh own that the infus i on of ozonized salinestrengt hens adaptable re actions of r esp iratory an d gas transpor t syst em s. Oz oneincreases the level of serotonin in the blood, decreases the frequency of respirationand increases volume of respiration and oxygen consumption.